Cytokine dynamics in the blood and cerebrospinal fluid of HIV/AIDS patients with cryptococcal meningitis receiving antifungal therapy - Su, Rui; Zhao, Shuwei; Liu, Jun; Li, Chongxi; Li, Yuye; Cao, Yingkui; Yang, Zhenghui; Li, Hongbin (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundCytokines in the serum and cerebrospinal fluid (CSF) are critical to the pathogenesis of HIV-associated cryptococcal meningitis (HCM). Previous studies focused on baseline cytokine levels, but changes during antifungal therapy are underexplored.MethodsTwenty-three patients with a first episode of HCM were prospectively followed to evaluate immune cell and cytokine dynamics during antifungal treatment therapy. Clinical features and laboratory data were systematically collected, and principal component and correlation analyses were performed to identify immune factors associated with HCM.ResultsTypical clinical manifestations include fever, headache, and nausea, among others. All patients presented severely low CD4+ T-cell counts and a notable reduction in CD8+ T cells. Over 28 days of antifungal treatment, significant decreases in the CSF levels of IL-2 and IL-10 and the plasma levels of IL-10 and IL-4 were observed. The plasma TNF-α concentration remained stable from days 1 to 14, followed by a marked increase on day 21. Plasma IFN-γ was negatively correlated with neutrophils (P = 0.04, r = -0.297), while IL-1β was positively correlated with leukocytes (P = 0.0031, r = 0.4266), and IL-8 was negatively correlated with lymphocytes (P = 0.0074, r = 0.3901). No significant correlations were found between other factors and neutrophils, leukocytes, or lymphocytes (P > 0.05).ConclusionCytokines derived from innate immune cells play a central role in host defense against HIV-associated cryptococcal infections. The observed reductions in cytokine levels in both plasma and CSF after antifungal therapy provide new insights into the immune response in HCM, highlighting the dynamic interplay of immune factors during treatment.